Analytic study of Soret and Dufour effects on heat destructive Casson liquid movement past an infinite vertical plate - Malapati, Venkateswarlu; P, Rami Reddy; K, Jaya Lakshmi (Journal of Naval Architecture and Marine Engineering, 2024)
This article describes a scientific solution of an unsteady movement of a Casson liquid in an infinite vertical plate in the proxy mity of Soret and Dufour implementations. The non-dimensional structure of mathematical equations is integrated with convenient initial and boundary limitations by applying Laplace transform technique. The expressions for Casson liquid motion, temperature, concentration, Skin-friction, heat and mass transfer coefficients are displayed. In the course of discussions, the effects of main parameters are described. The liquid motion, temperature, and concentration profiles are presented graphically for Pr = 1 and Sc = 0.22 as well as for arbitrary values of other parameters. The study is significant in the application areas of chemical analysis and biological analysis, drug delivery, bacteria detection and some others. A comparative analysis of the current research with previously published work is presented. Journal of Naval Architecture and Marine Engineering, 21 (1), 2024, pp. 27–40